An Overview of Position & Role of Women’s In Islam and In Pashtun Society - Qadir, Shukriya (sourcecoder, 2024)
Women are thought to be symbols of sacrifice and devotion Islam in Pashtun society, with the expectations of unquestioned obedience. The position of female was very low before Islam. Islam gives importance and ranked to women. In the Holy Quraan and many Hadiths Women and Men have equal status. Women are seen as the living essence of their family and are either protected or sacrificed for the honor of the family. They do not have the equal opportunity to live their own lives independently in Pashtun society.